2010
DOI: 10.1124/jpet.110.166793
|View full text |Cite
|
Sign up to set email alerts
|

Type 7 Adenylyl Cyclase-Mediated Hypothalamic-Pituitary-Adrenal Axis Responsiveness: Influence of Ethanol and Sex

Abstract: Although ethanol has been considered to be an anxiolytic agent, consumption of ethanol has also been shown to increase plasma adrenocorticotropin and glucocorticoids. The corticotrophin-releasing factor (CRF) receptor 1␣ (CRF-R1) is a G protein-coupled receptor that activates adenylyl cyclase (AC), leading to adrenocorticotropin (and subsequently glucocorticoid) release into the circulation. There are nine members of the membrane-bound AC family, and the type 7 AC (AC7) is most sensitive to ethanol, which enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Recent data suggest that CRF1 activation increases the enzymatic activity of AC7 (Antoni et al, 2003; Pronko et al, 2010). Therefore, we explored the possible role of AC7 in CRF-dependent stimulation of GABA release in the CeA.…”
Section: Resultsmentioning
confidence: 99%
“…Recent data suggest that CRF1 activation increases the enzymatic activity of AC7 (Antoni et al, 2003; Pronko et al, 2010). Therefore, we explored the possible role of AC7 in CRF-dependent stimulation of GABA release in the CeA.…”
Section: Resultsmentioning
confidence: 99%
“…AIP protein was also found to interact with two specific Ga 13 and Ga q . Although these two proteins were initially thought to have no effect on cAMP signalling, one study reported that Ga 13 activates an isoform of adenylate cyclase, type VII (AC7), which is partially responsible for cAMP production in a number of cells, including the pituitary (Jiang et al 2007, Pronko et al 2010. Given the lack of data with regard to interaction of the AIP protein with these four proteins, the effect of overexpression or knock down of AIP on cAMP signalling is a matter of speculation.…”
Section: Discussionmentioning
confidence: 99%
“…cAMP is produced from ATP by adenylyl cyclase, a large family of proteins including ten isoforms encoded by ten different genes and classified in five families (reviewed by Sunahara & Taussig (2002)). Mouse pituitaries express mRNA for adenylyl cyclase isoforms II, III, VI, and VII (Pronko et al 2010), depending on the cell type. In particular, GHproducing cells (GH1 2 C 1 cells) mainly contain adenylyl cyclase types I, III (calcium-calmoduline sensitive), and VI, whereas cells predominantly secreting PRL express adenylyl cyclase types II, IV, and VI (GH3 and GH4C1 cells) and type VIII (GH3B6 cells) (Paulssen et al 1994, Wachten et al 2010.…”
Section: Introductionmentioning
confidence: 99%